Analysis and Design of Marine Tourism Information System Using Rapid Application Development - Puspitarini, Titis; Christanto, Henoch Juli; Singgalen, Yerik Afrianto (Journal of Information System and Informatics, 2024)
The research addresses the growing need for efficient management of marine tourism activities in Indonesia, explicitly diving, snorkeling, and fishing. With the rapid expansion of marine tourism, there is a pressing need for innovative solutions to streamline information dissemination and enhance tourist experiences. This study proposes the development of a database and information system utilizing the Rapid Application Development (RAD) methodology to cater to the diverse needs of tourists engaging in marine activities. The Rapid Application Development approach comprises requirement planning, user design, construction, and cutover phases. Oracle Apex serves as the primary instrument for database design and system development. The findings suggest that implementing digital innovation in the form of information systems and databases significantly enhances the tourist experience in marine tourism destinations. Integrating GIS technology enables the visualization of location maps and valuable information, enriching the user experience and facilitating informed decision-making processes. Test results indicate that the application functions optimally and can be utilized effectively for destination management in Indonesia, emphasizing the practical implications of digital innovation in the tourism sector. In conclusion, designing and implementing a database and information system for marine tourism activities offer substantial benefits for destination management and tourist experiences in Indonesia. This research underscores the importance of technological advancements in optimizing destination management and fostering sustainable tourism development in coastal regions.